Method for preparing modified Prussian blue sodium battery positive electrode material and positive electrode material prepared by method
By forming a CuFeS2 cladding layer on the surface of Prussian blue sodium electropositive electrode material, the material has high water absorption, low conductivity and sensitivity to electrolyte, and significantly improves its rate performance, cycle stability and low temperature performance.
Patent Information
- Application Number
- CN202411442489.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-21
AI Technical Summary
Prussian blue sodium electropositive electrode materials have problems such as high water absorption, low conductivity and sensitivity to electrolytes, resulting in poor rate performance and cycle stability.
The CuFeS2 coating layer is formed on the surface of Prussian blue sodium electropositive electrode material through a liquid deposition coating process, improving the structural and interface stability of the material, improving conductivity and water absorption resistance.
It effectively reduces the water absorption of the material, improves its rate performance and cycle stability, enhances Coulomb efficiency, and improves low-temperature performance.
Smart Images

Figure CN119490230A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion batteries, and in particular relates to a method for preparing a modified Prussian blue sodium-ion positive electrode material and a positive electrode material prepared by the method. Background Art
[0002] With the gradual implementation of the "dual carbon" strategy, countries around the world have reached a consensus on vigorously developing new clean and renewable energy sources to build a diversified energy supply system. However, new energy sources such as solar energy, wind energy, and tidal energy have problems such as regionality, intermittency, and randomness, and cannot meet the requirements of energy consumption demand for stability, reliability, and other aspects. The development of low-cost, high-performance, and sustainable energy storage technologies has become an urgent problem that countries must solve in implementing the "dual carbon" strategy. In this context, electrochemical energy storage technologies represented by lithium-ion batteries have rapidly iterated and have become the new main force in the energy storage market in recent years. However, due to the relatively limited reserves of lithium resources and uneven geographical distribution, people have concerns about the development prospects of lithium-ion batteries in the field of large-scale energy storage. Sodium-ion batteries are similar to lithium-ion batteries in principle. Sodium resources are abundant, easily available, and widely distributed, so they are considered to be one of the most promising next-generation large-scale energy storage technologies.
[0003] The energy density of sodium-ion batteries is slightly inferior to that of lithium-ion batteries, while the production cost is lower than that of lithium iron phosphate batteries. The positive electrode material is one of the key components of sodium-ion batteries, which greatly affects the energy density and power density of the battery. The development progress of positive electrode materials directly determines the penetration of sodium-ion batteries in various application scenarios. Common positive electrode materials for sodium-ion batteries mainly include layered transition metal oxides, polyanionic compounds, Prussian blue compounds, etc. Prussian blue-based sodium-based positive electrode materials are materials with an open framework structure formed by metal-cyanide coordination bonds. Their structural characteristics have enough space to accommodate sodium ions, so they can easily undergo reversible ion insertion / extraction reactions. They are one of the few materials that can accommodate larger alkaline cations (such as Na + and K +) is one of the positive electrode matrix materials. Due to the simple synthesis, low cost and good structural stability of this type of material, Prussian blue sodium-based positive electrode materials are considered to be one of the most promising sodium-based positive electrode materials. However, due to the presence of more crystal water and defects in the crystal structure of the material, the sodium content of the material is low and the structure is easily unstable, and the actual capacity of the material is not high. Although the crystal water in the crystal structure can be removed by heat treatment, the material will absorb water again when exposed to the air again, which seriously affects the electrochemical properties and processing properties of the material. In addition, the poor electronic conductivity of the material itself and the side reactions between the electrode and the electrolyte often cause Prussian blue sodium-based positive electrode materials to have shortcomings such as poor rate performance and cycle stability, low Coulomb efficiency and obvious potential polarization. Therefore, how to improve the structure and interface stability of Prussian blue sodium-based positive electrode materials has become a key issue that needs to be urgently solved in academia and industry.
[0004] The problem of poor electrochemical kinetics and stability caused by sensitivity to electrolyte can be solved by surface coating modification, thereby improving the electrochemical performance of the material. Chinese patent documents with publication numbers CN113921798A, CN115411260A and CN114620758A disclose technical means for coating a layer of oxide on the surface of Prussian blue sodium positive electrode materials. After surface coating modification with oxide, Prussian blue sodium positive electrode materials avoid direct contact with electrolyte and air, improve interface stability and inhibit water absorption, and improve the cycle performance of the material. However, the conductivity of the coated oxide is extremely low, which cannot solve the problem of its inherent low conductivity. Wrapping on the surface of the material is not conducive to the transmission of electrons and affects the rate performance of the material.
[0005] In order to simultaneously solve the problems of poor electrochemical kinetics and stability caused by the inherent low conductivity and sensitivity to electrolyte of Prussian blue sodium cathode materials, and to improve the rate performance and cycle performance of the materials, it is necessary to find a modified material with stable structure and high conductivity for surface coating modification. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a modified Prussian blue sodium-based positive electrode material, which can achieve the beneficial effect of reducing the water absorption of the Prussian blue sodium-based positive electrode material and simultaneously solve the problems of poor electrochemical kinetics and stability caused by the inherent low conductivity and sensitivity to electrolyte of the Prussian blue sodium-based positive electrode material. The method is a liquid phase deposition coating process with simple process and suitable for large-scale production. The purpose of the present invention is also to provide a modified Prussian blue sodium-based positive electrode material prepared by the above method.
[0007] In order to solve the above technical problems, the technical solution provided by the present invention comprises the following steps: (1) Mixing deionized water and a Prussian blue sodium cathode material and ultrasonically dispersing the mixture for 2 to 8 hours to prepare a suspension A having a solid content of 5 to 75 wt %; (2) Soluble Cu 2+ Salt is added to the suspension A obtained in step (1), and the mass ratio of copper element to Prussian blue sodium positive electrode material is controlled to be 0.00346-0.0346:1 to obtain suspension B; the soluble Fe 3+ Salt is added to suspension B to control Cu 2+ with Fe 3+ The molar ratio is 0.5-3:1, and the mixture is stirred for 0.5-4h to obtain suspension C; (3) Configure soluble S 2- salt solution, and add it dropwise to the suspension C obtained in step (2) under stirring, and control S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 0.5-3:1, Fe 3+ and Cu 2+ Total moles and S 2- The molar ratio is 0.5 to 3:1, and a suspension D is obtained; (4) transferring the suspension D to a reactor and performing a hydrothermal reaction to obtain a precipitate; (5) Wash the precipitate obtained in step (4) with deionized water and ethanol, and vacuum dry the washed precipitate to obtain a CuFeS2-coated modified Prussian blue sodium-based positive electrode material.
[0008] Preferably, in step (1), the Prussian blue sodium-based positive electrode material includes one of an iron-based Prussian blue sodium-based positive electrode material, an iron-manganese-based Prussian blue sodium-based positive electrode material, an iron-cobalt-based Prussian blue sodium-based positive electrode material, an iron-nickel-based Prussian blue sodium-based positive electrode material, and an iron-copper-based Prussian blue sodium-based positive electrode material.
[0009] Preferably, in step (1), the ultrasonic dispersion time is 3 to 7 hours; preferably, the ultrasonic dispersion time is 4 to 6 hours.
[0010] Preferably, in step (1), the solid content of the suspension A is 15-65wt%; preferably, the solid content of the suspension A is 40-50wt%.
[0011] Preferably, in step (2), the mass ratio of copper element to Prussian blue sodium cathode material is 0.00692 to 0.0277:1; preferably, the mass ratio of copper element to Prussian blue sodium cathode material is 0.0138 to 0.0208:1.
[0012] Preferably, in step (2), the soluble Cu 2+The salt includes one of copper chloride, copper nitrate, copper acetate, and copper sulfate; preferably soluble Cu 2+ The salt includes one of copper chloride, copper acetate, and copper sulfate; more preferably soluble Cu 2+ The salt is copper chloride.
[0013] Preferably, in step (2), Cu 2+ with Fe 3+ The molar ratio is 0.6 to 2:1; preferably Cu 2+ with Fe 3+ The molar ratio is 0.9 to 1.1:1.
[0014] Preferably, in step (2), the soluble Fe 3+ The salt includes one of ferric chloride, ferric nitrate, ferric sulfate, and ferric acetate; preferably soluble Fe 3+ The salt includes one of ferric chloride and ferric sulfate; more preferably soluble Fe 3+ The salt is iron sulfate.
[0015] Preferably, in step (2), the stirring time is 1 to 3 hours; preferably, the stirring time is 1.5 to 2.5 hours.
[0016] In the step (3), the soluble S 2- The salt includes one of sodium sulfide, sodium thiosulfate, thiourea, ammonium sulfide, and thioacetamide; preferably soluble S 2- The salt includes one of sodium sulfide, sodium thiosulfate, and thiourea; more preferably, soluble S 2- The salt is thiourea.
[0017] Preferably, in step (3), the soluble S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 0.75 to 2.75:1; preferably, the soluble S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 1 to 1.5:1.
[0018] Preferably, in step (3), Fe 3+ and Cu 2+ Total moles and S 2- The molar ratio is 0.7 to 1.5:1; preferably Fe 3+ and Cu 2+ Total moles and S 2- The molar ratio is 0.9 to 1.1:1.
[0019] Preferably, in step (3), the stirring speed is 50 to 850 r / min; preferably, the stirring speed is 400 to 800 r / min; more preferably, the stirring speed is 550 to 650 r / min.
[0020] Preferably, in step (3), the soluble S 2- The salt solution drop rate is 2-60 ml / min; preferably soluble S 2- The salt solution drop rate is 20 to 50 ml / min; more preferably, soluble S 2- The salt solution dropping speed is 30-40 ml / min.
[0021] Preferably, in step (4), the hydrothermal reaction temperature is 150-260°C; preferably, the hydrothermal reaction temperature is 180-240°C; more preferably, the hydrothermal reaction temperature is 190-210°C.
[0022] Preferably, in step (4), the hydrothermal reaction time is 4 to 20 h; preferably, the hydrothermal reaction time is 9 to 18 h; more preferably, the hydrothermal reaction time is 13 to 15 h.
[0023] Preferably, in step (5), the vacuum drying temperature is 120-230°C; preferably, the vacuum drying temperature is 140-190°C; more preferably, the vacuum drying temperature is 150-170°C.
[0024] Preferably, in step (5), the vacuum drying time is 10 to 26 hours; preferably, the vacuum drying time is 14 to 20 hours; more preferably, the vacuum drying time is 16 to 18 hours.
[0025] The present invention also provides a modified Prussian blue sodium-based positive electrode material, which is prepared by the above method; the positive electrode material comprises a Prussian blue sodium-based positive electrode material matrix and a CuFeS2 coating layer.
[0026] Since a CuFeS2 coating layer is formed on the surface of the Prussian blue sodium-based cathode material by a liquid phase deposition coating process, the method provided by the present invention and the obtained modified Prussian blue sodium-based cathode material have the following beneficial effects: (1) CuFeS2 is insoluble in water. This technical solution uses a liquid phase deposition coating process to coat a layer of CuFeS2 on the surface of the Prussian blue sodium cathode material, which can avoid direct contact between the base material and moisture in the air, reduce its water absorption, and improve the processing performance of the material.
[0027] (2) The presence of CuFeS2 can prevent the Prussian blue sodium cathode material matrix from direct contact with the electrolyte, significantly inhibit the occurrence of interfacial side reactions, solve the problems of poor electrochemical kinetics and stability caused by the matrix's sensitivity to the electrolyte, increase the material's interfacial stability, and thus improve the material's cycle performance.
[0028] (3) CuFeS2 can provide more abundant redox reaction sites. Its crystal structure can reversibly deintercalate lithium and sodium, and has a very high theoretical capacity. It is a class of lithium / sodium ion battery electrode active materials with great application prospects. The CuFeS2 coating layer can provide additional sodium ion deintercalation active sites during the charge and discharge process, reduce the irreversible capacity caused by the coating, and improve the coulombic efficiency of the material.
[0029] (4) CuFeS2 is a degenerate semiconductor with good optical, electrical and magnetic properties, high conductivity and stable chemical properties. At room temperature, its conductivity is 10 -1 S / cm, which is much higher than common metal oxides. In addition, CuFeS2 is similar to metals and shows higher electronic conductivity as the temperature decreases. At 100K, its conductivity is 10 3 S / cm. These advantages make it considered to be an ideal surface modification material. Coating CuFeS2 on the surface of the base material can solve the problems of poor electrochemical kinetics and stability caused by the inherent low conductivity of Prussian blue sodium cathode materials, thereby improving the rate performance of the material. In addition, as the temperature decreases, the electronic conductivity of CuFeS2 increases, which also helps to improve the low-temperature performance and charging and discharging performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The charge-discharge curves of the modified Prussian blue sodium-based cathode material prepared in Example 1 of the present invention and the iron-manganese-based Prussian blue sodium-based cathode material prepared in Comparative Example 1 at 0.1C; Figure 2 The X-ray diffraction (XRD) diagram of the modified Prussian blue sodium-based cathode material prepared in Example 1 of the present invention; Figure 3 This is a scanning electron microscope (SEM) image of the modified Prussian blue sodium-based cathode material prepared in Example 1; Figure 4 This is a scanning electron microscope (SEM) image of the iron-manganese-based Prussian blue sodium-based positive electrode material without any treatment in Comparative Example 1 of the present invention; Figure 5 This is an electronic image collected when performing energy dispersive X-ray spectroscopy analysis on the modified Prussian blue sodium-based cathode material prepared in Example 1 of the present invention; Figure 6 for Figure 5 Energy dispersive X-ray spectroscopy (EDS) of selected areas. DETAILED DESCRIPTION
[0031] In order to make the present invention more obvious and easy to understand, the technical solution of the present invention is further explained below through embodiments in combination with the drawings, but it is not intended to limit the protection scope of the present invention.
[0032] In the present invention, the Prussian blue sodium positive electrode material includes but is not limited to one of an iron-based Prussian blue material, an iron-manganese-based Prussian blue material, an iron-cobalt-based Prussian blue material, an iron-nickel-based Prussian blue material, and an iron-copper-based Prussian blue material. The Prussian blue sodium positive electrode material selected in the embodiment of the present invention is an iron-manganese-based Prussian blue material. The specific synthesis process is as follows: (1) Using manganese sulfate and sodium ferrocyanide decahydrate as solutes and distilled water as solvent, prepare 300 ml of 0.1 mol / L manganese sulfate solution and sodium ferrocyanide solution respectively; (2) Dissolve sodium chloride in 50 mL of distilled water to prepare a solution with a molar concentration of 0.5 mol / L; (3) using a peristaltic pump to add the manganese sulfate solution and sodium ferrocyanide solution dropwise to the sodium chloride solution under magnetic stirring at 60° C. at a rate of 5 ml / min to form a milky white suspension. After the addition is completed, the milky white suspension is stirred for 5 h. (4) After stopping stirring, the obtained suspension was centrifuged to obtain a milky white precipitate, which was washed three times with deionized water and anhydrous ethanol respectively, and then the precipitate was vacuum dried at 150° C. for 12 hours to obtain an uncoated and modified iron-manganese-based Prussian blue sodium-based positive electrode material. Example 1
[0033] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 5 hours to obtain a suspension A with a solid content of 45wt%. The mass ratio of copper element to the iron-manganese-based Prussian blue sodium-based cathode material was controlled to be 0.0173:1, and an appropriate amount of copper chloride was added to the suspension A to obtain a suspension B. 2+ with Fe 3+ The molar ratio is 1:1, and an appropriate amount of ferric sulfate is added to suspension B and stirred for 2 hours to obtain suspension C. Control S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 1.25:1, Fe 3+ and Cu 2+ Total moles and S 2-The molar ratio is 1:1, thiourea solution is prepared, and it is added dropwise to suspension C at 35 ml / min under stirring at 600 r / min to obtain suspension D. Suspension D is transferred to a reactor, and a hydrothermal reaction is carried out at 200°C for 14 hours to obtain a precipitate, which is then washed with deionized water and ethanol. The washed precipitate is vacuum dried at 160°C for 17 hours to obtain a modified Prussian blue sodium-based cathode material.
[0034] During the modification process, Fe in suspension C 3+ and Cu 2+ With the dripping S 2- S in salt solution 2- After further hydrothermal reaction at 200℃ for 14h, CuFeS2 is formed to be coated on the surface of the iron-manganese-based Prussian blue sodium-based cathode material. The CuFeS2 coating layer obtained by the hydrothermal reaction has a relatively high crystallinity and high structural stability, which is conducive to better achieving the purpose of coating modification to improve the electrochemical performance of the material.
[0035] The CuFeS2 coated on the surface of the iron-manganese-based Prussian blue sodium cathode material is insoluble in water, which can prevent the base material from direct contact with moisture in the air, reduce its water absorption, and improve the processing performance of the material. The presence of CuFeS2 can prevent the base material of the Prussian blue sodium cathode material from direct contact with the electrolyte, significantly inhibit the occurrence of interfacial side reactions, solve the problem of poor electrochemical kinetics and stability caused by the sensitivity of the base material to the electrolyte, increase the interfacial stability of the material, and thus improve the material's cycle performance. The CuFeS2 coating layer is electrochemically active, and can provide additional sodium ion deintercalation active sites during the charge and discharge process, reduce the irreversible capacity caused by the coating, and improve the coulombic efficiency of the material. CuFeS2 has a high conductivity of up to 10 -1 S / cm room temperature conductivity, coated on the surface of the base material can solve the problem of poor electrochemical kinetics and stability caused by the inherent low conductivity of Prussian blue sodium cathode materials, thereby improving the rate performance of the material. In addition, as the temperature decreases, CuFeS2 exhibits higher electronic conductivity. At 100K, its conductivity is 10 3 S / cm, which also helps to improve the battery's low temperature performance and charging and discharging performance.
[0036] Figure 1The first charge and discharge curves of the materials obtained in Example 1 and Comparative Example 1 at 0.1C are shown. It can be seen from the figure that the 0.1C discharge capacity of the material in Example 1 is about 4 mAh / g higher than that in Comparative Example 1. In addition, the coulombic efficiency of the first charge and discharge of the material obtained in Example 1 is 97.4%, while the first efficiency of the material in Comparative Example 1 is only 90.4%. This shows that after the CuFeS2 coating modification, the problem of poor electrochemical kinetics and stability caused by the sensitivity of the substrate to the electrolyte is solved, the interface stability of the material is increased, and the side reaction between the electrolyte and the interface is suppressed during the charge and discharge process.
[0037] Figure 2 The X-ray diffraction (XRD) diagram of the modified Prussian blue sodium-based positive electrode material prepared in Example 1 of the present invention shows that the structure of the material does not change after the CuFeS2 coating modification, and the main characteristic peaks in the X-ray diffraction (XRD) diagram correspond to the iron-manganese-based Prussian blue sodium-based positive electrode material, indicating that this technical solution will not destroy the structure of the material and cause it to lose its electrochemical activity. A weak characteristic peak of copper-based sulfide CuFeS2 appears at 29.7°, which indicates that this technical solution successfully forms a CuFeS2 coating layer on the surface of the Prussian blue sodium-based positive electrode material. Example 2
[0038] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 4 hours to obtain a suspension A with a solid content of 40wt%. The mass ratio of copper element to the iron-manganese-based Prussian blue sodium-based cathode material was controlled to be 0.0208:1, and an appropriate amount of copper sulfate was added to the suspension A to obtain a suspension B. 2+ with Fe 3+ The molar ratio is 0.9:1, and an appropriate amount of ferric chloride is added to suspension B and stirred for 1.5 hours to obtain suspension C. Control S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 1:1, Fe 3+ and Cu 2+ Total moles and S 2- The molar ratio is 0.9:1, a sodium thiosulfate solution is prepared, and it is added dropwise to the suspension C at 30 ml / min under the stirring condition of 550 r / min to obtain a suspension D. The suspension D is transferred to a reactor, and a hydrothermal reaction is carried out at 190°C for 15 hours to obtain a precipitate, which is then washed with deionized water and ethanol. The washed precipitate is vacuum dried at 170°C for 16 hours to obtain a CuFeS2-coated modified iron-manganese-based Prussian blue sodium-based positive electrode material. Example 3
[0039] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 6 hours to obtain a suspension A with a solid content of 50wt%. The mass ratio of copper element to the iron-manganese-based Prussian blue sodium-based cathode material was controlled to be 0.0138:1, and an appropriate amount of copper acetate was added to the suspension A to obtain a suspension B. 2+ with Fe 3+ The molar ratio is 1.1:1. Add an appropriate amount of ferric nitrate to suspension B and stir for 2.5 hours to obtain suspension C. Control S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 1.5:1, Fe 3+ and Cu 2+ Total moles and S 2- The molar ratio is 1.1:1, a sodium sulfide solution is prepared, and it is added dropwise to the suspension C at 40 ml / min under the stirring condition of 650 r / min to obtain a suspension D. The suspension D is transferred to a reactor, and a hydrothermal reaction is carried out at 210°C for 13 hours to obtain a precipitate, which is then washed with deionized water and ethanol. The washed precipitate is vacuum dried at 150°C for 18 hours to obtain a CuFeS2-coated modified iron-manganese-based Prussian blue sodium-based positive electrode material. Example 4
[0040] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 3 hours to obtain a suspension A with a solid content of 15wt%. The mass ratio of copper element to the iron-manganese-based Prussian blue sodium-based cathode material was controlled to be 0.00692:1, and an appropriate amount of copper nitrate was added to the suspension A to obtain a suspension B. 2+ with Fe 3+ The molar ratio is 2:1, and an appropriate amount of ferric sulfate is added to suspension B and stirred for 1 hour to obtain suspension C. Control S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 0.75:1, Fe 3+ and Cu 2+ Total moles and S 2- The molar ratio is 1.5:1, and an ammonium sulfide solution is prepared and added to the suspension C at 20 ml / min under stirring at 400 r / min to obtain a suspension D. The suspension D is transferred to a reactor and subjected to a hydrothermal reaction at 180°C for 18 hours to obtain a precipitate, which is then washed with deionized water and ethanol. The washed precipitate is vacuum dried at 190°C for 14 hours to obtain a modified Prussian blue sodium-based cathode material. Example 5
[0041] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 7 hours to obtain a suspension A with a solid content of 65wt%. The mass ratio of copper element to the iron-manganese-based Prussian blue sodium-based cathode material was controlled to be 0.0277:1, and an appropriate amount of copper chloride was added to the suspension A to obtain a suspension B. 2+ with Fe 3+ The molar ratio is 0.6:1, and an appropriate amount of ferric sulfate is added to suspension B and stirred for 3 hours to obtain suspension C. Control S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 2.75:1, Fe 3+ and Cu 2+ Total moles and S 2- The molar ratio is 0.7:1, and a thioacetamide solution is prepared and added to the suspension C at 50 ml / min under stirring at 800 r / min to obtain a suspension D. The suspension D is transferred to a reactor and subjected to a hydrothermal reaction at 240°C for 9 hours to obtain a precipitate, which is then washed with deionized water and ethanol. The washed precipitate is vacuum dried at 140°C for 20 hours to obtain a modified Prussian blue sodium-based cathode material. Example 6
[0042] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 8 hours to obtain a suspension A with a solid content of 75wt%. The mass ratio of copper element to the iron-manganese-based Prussian blue sodium-based cathode material was controlled to be 0.00346:1, and an appropriate amount of copper chloride was added to the suspension A to obtain a suspension B. 2+ with Fe 3+ The molar ratio is 0.5:1, and an appropriate amount of ferric sulfate is added to suspension B and stirred for 4 hours to obtain suspension C. Control S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 3:1, Fe 3+ and Cu 2+ Total moles and S 2- The molar ratio is 0.5:1, and a thiourea solution is prepared and added to the suspension C at 2 ml / min under stirring at 850 r / min to obtain a suspension D. The suspension D is transferred to a reactor and subjected to a hydrothermal reaction at 150°C for 20 h to obtain a precipitate, which is then washed with deionized water and ethanol. The washed precipitate is vacuum dried at 230°C for 10 h to obtain a modified Prussian blue sodium-based cathode material. Example 7
[0043] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 2 hours to obtain a suspension A with a solid content of 15wt%. The mass ratio of copper element to the iron-manganese-based Prussian blue sodium-based cathode material was controlled to be 0.0346:1, and an appropriate amount of copper chloride was added to the suspension A to obtain a suspension B. 2+ with Fe 3+ The molar ratio is 3:1, and an appropriate amount of ferric sulfate is added to suspension B and stirred for 0.5 h to obtain suspension C. Control S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 0.5:1, Fe 3+ and Cu 2+ Total moles and S 2- The molar ratio is 3:1, and a thiourea solution is prepared and added to the suspension C at 60 ml / min under a stirring condition of 50 r / min to obtain a suspension D. The suspension D is transferred to a reactor and subjected to a hydrothermal reaction at 260°C for 4 h to obtain a precipitate, which is then washed with deionized water and ethanol. The washed precipitate is vacuum dried at 120°C for 26 h to obtain a modified Prussian blue sodium-based cathode material.
[0044] In order to illustrate the necessity of each technical link of the present invention for the beneficial effects, the following comparative examples are implemented. Comparative Example 1
[0045] An iron-manganese-based Prussian blue sodium-based positive electrode material without any treatment was used as Comparative Example 1. Comparative Example 2
[0046] Deionized water and the iron-manganese-based Prussian blue sodium-based cathode material were mixed and ultrasonically dispersed for 5 hours to obtain a suspension A with a solid content of 45wt%; the mass ratio of copper element to the iron-manganese-based Prussian blue sodium-based cathode material was controlled to be 0.0399:1, copper chloride was added to the suspension A and stirred for 2 hours to obtain a suspension B; a NaHCO3 solution was prepared, and the NaHCO3 solution and the soluble Cu 2+ The salt solution concentration ratio is 1.25:1, Cu 2+ The molar ratio of NaHCO3 is 1:2, and it is added dropwise to suspension B at 35 ml / min under stirring at 600 r / min to obtain suspension C; the suspension C is transferred to a reactor, and a hydrothermal reaction is carried out at 150°C for 12 hours to obtain a precipitate, which is then washed with deionized water and ethanol. The washed precipitate is heat-treated at 160°C for 17 hours under nitrogen as a protective gas to obtain a copper-based oxide surface-coated modified iron-manganese-based Prussian blue sodium-based positive electrode material.
[0047] The material prepared by the process of the embodiment and the comparative example is immediately used as an active material to prepare a positive electrode sheet for the assembly test of a sodium ion battery.
[0048] The preparation process of the positive electrode is as follows: the positive electrode is composed of four parts: active material, conductive agent, binder and current collector. Acetylene black is used as the conductive agent, 10mg / ml polyvinylidene fluoride (PVDF) N-methylpyrrolidone (NMP) solution is used as the binder, the active material, conductive agent and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 7:2:1 and ground into a slurry with suitable viscosity, and then the slurry is evenly coated on the aluminum foil. The coated electrode is placed in a vacuum drying oven at 120°C and dried for 8 hours. After drying, it is punched into a small disc with a diameter of 12mm by a punching machine, and finally the battery is assembled in a glove box in an argon atmosphere.
[0049] The battery assembly process is as follows: the prepared positive electrode sheet is used as the positive electrode, the metal sodium sheet is used as the negative electrode, the diaphragm is a glass fiber diaphragm, 250 μL of 1 mol / L sodium hexafluorophosphate electrolyte is added, the electrolyte solvent is a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1, and 2% fluoroethylene carbonate (FEC) is added to the electrolyte as an additive. The button half-cell is assembled in the order of the negative electrode shell, sodium sheet, diaphragm, positive electrode, gasket, shrapnel, and positive electrode shell, and finally packaged using an electric button battery sealing machine.
[0050] The assembled button half-cell adopts constant current charge and discharge mode in the voltage range of 2.0 to 4.0 V to carry out corresponding electrochemical performance tests.
[0051] In addition, in order to test the storage performance of the material, the materials prepared by the process of Example 1 and Comparative Example 1 were exposed to air for 15 hours to prepare electrode sheets and assembled batteries for corresponding electrochemical performance tests. The samples were marked as Example 1-15h and Comparative Example 1-15h, respectively.
[0052] In addition, to test the low temperature performance, the electrode sheets assembled with the materials of Example 1 and Comparative Example 1 were subjected to electrochemical performance testing at -10°C, and the battery performances were marked as Example 1-(-10°C) and Comparative Example 1-(-10°C), respectively.
[0053] The electrochemical performance test results of each material are shown in Table 1.
[0054]
[0055] The performance of Examples 1 to 7 and Comparative Example 2 are better than that of Comparative Example 1, which shows that no matter what material is coated on the surface, the electrochemical performance of the material can be significantly improved. Among all the embodiments, Example 1 has the best electrochemical performance. By comparing the discharge specific capacity of Example 1 and Comparative Example 2, it can be seen that the capacity difference is relatively small during 0.1C discharge, but the capacity difference becomes larger during high-rate discharge. At 10C and 20C, the discharge specific capacity of Example 1 is 24.8mAh / g and 29.9mAh / g higher than that of Comparative Example 2, respectively. This shows that the C-modified Prussian blue sodium-based electrical material prepared by this process scheme has high electrical conductivity, which solves the problem of poor electrochemical kinetics and stability caused by the inherent low electrical conductivity of Prussian blue sodium-based positive electrode materials, thereby improving the rate performance of the material. The difference in discharge capacity at different rates from 0.1C to 20C for Example 1 and the samples after being set aside for 15 hours does not exceed 1 mAh / g, and the difference in retention rate at 10C cycle for 1500 weeks does not exceed 1%; the difference in discharge capacity at different rates for the samples of Comparative Example 1 set aside for 15 hours is relatively large, with a capacity difference of up to 19 mAh / g at 10C discharge, a capacity difference of up to 24 mAh / g at 20C discharge, and a retention rate difference of more than 11.3% at 10C cycle for 1500 weeks, which indicates that the use of this technical solution to coat the Prussian blue sodium positive electrode material with CuFeS2 can modify and inhibit the material from absorbing water again in the air, improve the storage stability of the material in the air, and help improve the processing performance of the material. The low-temperature performance of Example 1 and Comparative Example 1 was tested at -10°C. By comparison, it can be seen that Example 1 is better than Comparative Example 1, which indicates that the property of CuFeS2 that the conductivity increases as the temperature decreases helps to improve the low-temperature performance of the battery.
[0056] The 10C cycle 1500 cycle capacity retention rate of each embodiment is not less than 88%, and the 20C high discharge capacity is greater than 112 mAh / g, which is better than the comparative example. From these two points of comparison, it can be seen that the presence of CuFeS2 formed on the surface of the material using the technical solution of the present invention can solve the problems of poor electrochemical kinetics and stability caused by the inherent low conductivity and sensitivity to electrolyte of Prussian blue sodium positive electrode materials, thereby improving the rate performance and cycle performance of the material.
[0057] The above-described specific embodiments further illustrate the present invention in detail, but these descriptions cannot be understood as limiting the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a modified Prussian blue sodium-based cathode material, characterized in that: The following steps are involved: (1) Mixing deionized water and a Prussian blue sodium cathode material and ultrasonically dispersing the mixture for 2 to 8 hours to prepare a suspension A having a solid content of 5 to 75 wt %; (2) Soluble Cu 2+ Salt is added to the suspension A obtained in step (1), and the mass ratio of copper element to Prussian blue sodium positive electrode material is controlled to be 0.00346-0.0346:1 to obtain suspension B; the soluble Fe 3+ Salt is added to suspension B to control Cu 2+ with Fe 3+ The molar ratio is 0.5-3:1, and the mixture is stirred for 0.5-4h to obtain suspension C; (3) Configure soluble S 2- salt solution, and add it dropwise to the suspension C obtained in step (2) under stirring, and control S 2- Fe in salt solution and suspension C 3+ and Cu 2+ The total molar concentration ratio of salt is 0.5-3:1, Fe 3+ and Cu 2+ Total moles and S 2- The molar ratio is 0.5 to 3:1, and a suspension D is obtained; (4) transferring the suspension D to a reactor and performing a hydrothermal reaction to obtain a precipitate; (5) Wash the precipitate obtained in step (4) with deionized water and ethanol, and vacuum dry the washed precipitate to obtain a CuFeS2-coated modified Prussian blue sodium-based positive electrode material.
2. The method for preparing a modified Prussian blue sodium-based cathode material according to claim 1, characterized in that: In the step (1), the Prussian blue sodium positive electrode material includes one of an iron-based Prussian blue sodium positive electrode material, an iron-manganese-based Prussian blue sodium positive electrode material, an iron-cobalt-based Prussian blue sodium positive electrode material, an iron-nickel-based Prussian blue sodium positive electrode material, and an iron-copper-based Prussian blue sodium positive electrode material.
3. The method for preparing a modified Prussian blue sodium-based cathode material according to claim 1, characterized in that: In the step (2), the soluble Cu 2+ The salt includes one of copper chloride, copper nitrate, copper acetate, and copper sulfate; soluble Fe 3+ The salt includes one of ferric chloride, ferric nitrate, ferric sulfate, and ferric acetate.
4. The method for preparing a modified Prussian blue sodium-based cathode material according to claim 1, characterized in that: In the step (3), the soluble S 2- The salt includes one of sodium sulfide, sodium thiosulfate, thiourea, ammonium sulfide, and thioacetamide; the stirring speed is 50-850r / min; S 2- The salt solution dropping speed is 2-60 ml / min.
5. The method for preparing a modified Prussian blue sodium-based cathode material according to claim 1, characterized in that: In the step (4), the hydrothermal reaction temperature is 150-260° C., and the hydrothermal reaction time is 4-20 hours.
6. The method for preparing a modified Prussian blue sodium-based cathode material according to claim 1, characterized in that: In the step (5), the vacuum drying temperature is 120 to 230° C., and the vacuum drying time is 10 to 26 hours.
7. A modified Prussian blue sodium-based cathode material, characterized in that: The CuFeS2 coated and modified Prussian blue sodium-based positive electrode material is prepared by the method described in any one of claims 1 to 6.
Citation Information
Patent Citations
Positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery
CN113921798A
Preparation method of copper oxide modified iron-based Prussian blue positive electrode material
CN114620758A
Gas phase modification method of Prussian blue sodium battery positive electrode material and positive electrode material prepared by same
CN115411260A